AAV capsids target muscle-resident cells with different efficiencies—A comparative study between AAV8, AAVMYO, and AAVMYO2 - Timothy J. McGowan; Nicolas Lewerenz; Eleonora Maino; Marco Thürkauf; Lena Jörin; Markus A. Rüegg (Molecular Therapy: Methods & Clinical Development)
Adeno-associated viruses (AAVs) of different serotypes are commonly used in gene therapies and gene interrogation studies to deliver transgenes to skeletal muscle in humans and mice. While efficient muscle fiber transduction is possible, little is known of their capacity to transduce muscle-residing mononuclear cells. Here, we addressed this question for AAV8 and the two myotropic AAVs, AAVMYO and AAVMYO2, by engineering them to express the tdTomato gene. AAVs were then injected intramuscularly or intravenously at two different doses into adult mice followed by flow-cytometry-based isolation of endothelial cells, immune cells, muscle stem cells, and fibro-adipogenic progenitor cells from the tibialis anterior muscle. Overall, we noted varying rates of tdTomato expression across all cell types. Transduction efficiency fluctuated in AAV serotype-dependent, titer-dependent, administration-dependent, and cell-dependent manners. By visualizing AAV DNA in vivo, we confirmed that AAV8, AAVMYO, and AAVMYO2 deliver transgenes to muscle-residing mononuclear cells. We show that mononuclear cells are also successfully transduced in the dyW/dyW mouse model of LAMA2-related muscular dystrophy. Altogether, we demonstrate that muscle-residing mononuclear cells are transduced by AAVs and provide an insightful guidance for researchers aiming to target muscle-resident mononuclear cells in their studies.